A Study to Explore Consumer Behavior Towards Fast Fashion Clothing Influenced by Social Media in Europe - Naghizade, Zamin (Digital Repository of Theses, 2026)
Background The research investigates upon influence of social media on consumer buying behavior within European fast fashion industry with a special focus on purchase decisions. At present social media platforms such as TikTok and Instagram emerging drastically as primary sources of fashion inspiration where brands increase readily rely upon digital content strategies to make their consumers more engaged and make a purchase. Therefore, the study examines the key factors including brand engagement, convenience, platform type, privacy and influencer endorsement to identify their impact on purchase intentions. The research has focused upon Technology acceptance model, Elaboration likelihood model, Social Influence theory and Consumer culture theory. Methods The research adopts a pragmatic research philosophy along with deductive approach and descriptive cross-sectional design. The data is collected using structured close ended questionnaire from a stratified random sample of 384 European social media uses. The quantitative analysis consists of SPSS which includes reliability, validity, correlation, regression and ANOVA tests to explore the relationship between the independent and dependent variables. Results Data analysis showed that the social media factors were statistically significant in regard to fast fashion purchasing behaviour among the European population. The mean scores of all constructs were moderate in nature, which indicated similar levels of influence. Correlation analysis showed that the consumer buying behavior and engagement with the brand (r =.674), the type of platform used (r =.668), and influencer endorsement (r =.618) are all positive and significant with p <.001. The regression analysis also showed that the model has a strong explanatory power as it accounts 69.7 %of variation in the consumer buying behavior. Discussion and Conclusion As it was discussed, the phenomenon of fast fashion buying via social media in Europe is complex and context specific. The nature of platforms and content type often dictate a swapping of impulse and planned purchases by consumers. Instagram and Tik Tok were identified to have a complementary effect, where Instagram is associated with using planned purchasing and Tik Tok is associated with using impulse purchasing. The social media involvement has a positive impact on the purchase decisions, but it should be supported by such factors like trust and convenience. The influencer marketing proved to have a stronger purchasing power as compared to the brand advertisement, whereas the celebrity endorsement had a greater influence as compared to the peer recommendation given the sense of aspiration. KEYWORDS Fast Fashion, Social Media, Europe, Brand engagement, Consumer behavior, Convenience, Privacy, Platform type, Influencer endorsement